Towards Environmental Sustainability: The Impact of External Debt and Government Expenditure on Carbon Emissions in Somalia - Warsame, Zakarie Abdi; Dirie, Ahmed Nur; Nor, Bile Abdisalan (International Journal of Energy Economics and Policy, 2024)
This study aims to assess the effect of external debt and government expenditure on carbon emissions in Somalia. To do so, the study employed a rigorous econometric approaches such as autoregressive distributed lag model (ARDL), Fully modified least square (FMOLS), and Dynamic least square (DOLS). Findings demonstrated that external debt (LNED) positively and significantly affects carbon emissions. Results revealed that a 1%, or a point increase of external debt, rises 0.29% into the emitted emissions. Moreover, the study found that the long-run coefficient of government expenditure (LNGE) positively correlates with emissions. However, a 1% increase in total government expenditure significantly increases CO2 emissions by 0.05% in the long run. So, regarding the positive correlation between external debt, government expenditure, and carbon emissions, the study suggests that the government should strategically use its expenditures and external debt to fund environmentally sustainable projects. This approach aims to reduce carbon emissions while promoting sustainable development and balancing economic growth with ecological conservation.